Вопросы интеграции детей с аутизмом - Асоян, Л. Э.
In the article are presented the main quest ions of inclusive education e© ecially of children with autism . On the basis of work in the article analized some approaches of education ,inclusion and social adaptation of these children.
Keywords: Аутизм